Enhancement magnetic properties of Malaysian iron ore by biomass treatment - Purwanto, Hadi (2014)
As the second largest producer of palm oil, biomass in Malaysia has been pyrolyzed for primary products like oil and produces significant amount of char containing carbon. This large portion of highly fine char particle that produced due to incomplete combustion is difficult to be disposed, possessing disposal and environmental problems. In this research, development process to treat the local low grade iron ore as iron resource has been proposed. Malaysian iron ore was treated by using EFB char as reductant and heating the sample at 600°C caused a change in phase from goethite to hematite but does not significantly improve the magnetic properties of the reduced ore. However, the presence of magnetite with rise of temperature up to 800°C remarkably enhances the magnetic properties of iron ore as it is counted as strong magnetic mineral. The magnetization diminishes as the ore was reduced into a partial of wustite at 900°C of reduction temperature. The magnetic susceptibility of artificial magnetite in reduced ore at 800°C approached the value of natural magnetite. The improvement of magnetic properties particularly at 800°C of reduction temperature show that EFB char has a potential to be used as reducing agent in iron making and the reduced ore could be a promising route for iron resource.